Fitpack Kit Detektor Keputihan Abnormal Secara Praktis dan Nyaman - Wahyuni, Siti Suci; Amalia, Fara Zhiniya; Prasanta, Made Radikia; Erawati, Nadya; Hamimi, Erti (citeus, 2022)
Based on WHO data, vaginal infections every year affect women worldwide, around 10-15 percent of 100 million women. Pathological vaginal infections caused by Bacterial vaginosis (BV), Candidiasis, and Trichomoniasis. Abnormal vaginal discharge is an indication of a reproductive tract infection. Therefore, it is very important for women to make early detection of vaginal discharge that they suffer from. However, many women underestimate the presence of vaginal discharge, this is because women have a sense of shame to carry out their genital examinations at doctors, especially by male doctors. In addition, most women do not like the examination using medical procedures because of the feeling of discomfort with the examination procedure. Because of this, in this expansion research, an ATMega 168-based detection device and an expert system-based application were designed forearly detection of vaginal discharge. The method used in this development research consists of several stages including: 1) needs analysis, 2) design, 3) design of vaginal discharge detection tools and applications, 4) testing, 5) evaluation. The results of this research and development resulted in a vaginal discharge detection tool along with an expert system-based leucorrhoea detection application with the certainty factor method.